Introduction to Companion Animal Gastro-Intestinal Endoscopy - Ilievska Ksenija , Novakov Todor , Trojachanec Snezana , Trojachanec Plamen (Faculty of Veterinary Medicine - Skopje, 2016)
Gastrointestinal endoscopy has generally become one of the most important diagnostic techniques for evaluation of patients with primary gastrointestinal abnormalities. It is a safe and effective diagnostic procedure of various gastrointestinal (GI) disorders however it should be used in conjunction with other diagnostic modalities. Endoscopy should not be a substitute for a complete work-up. GI endoscopy has many advantages including minimal morbidity and mortality as well as sensitivity for diagnosis of mucosa! disorders and foreign objects in the GI tract. One of the major advantages of endoscopy is its' minimal invasiveness, minimal preparation for urgent patients, except for the preparation for the mandatory anesthesia. Endoscopy allows a direct visualization of large portion of GI tract, collection of multiple mucosa! biopsy samples, brush cytology and fluid aspiration, many therapeutic procedures such as removal of mucosa! polyps and esophageal and gastric foreign bodies. Fastening of the patient should be done prior to the endoscopy to ensure proper examination. Usually the animals for esophagogastroduodenoscopy should be fasted at least 12 hours, and preferably for 24 hours, since delayed gastric emptying often occurs with GI disease. Animals undergoing for colonoscopy should be fasted for 36 to 48 hours and these animals should receive enemas up to 12 hours before the procedure. Endoscopic removal of a GI foreign body is the best example of the therapeutic potential for endoscopy. Most objects lodged in the esophagus, stomach, proximal duodenum, and colon can be removed via endoscopy with the exceptions of smooth objects that do not have any defects on their surface or bones that are deeply embedded into the wall of the GI tract. Lesions, such as neoplasia, superficial gastroenteritis, and Helicobacter spp colonization can be detected via endoscopic biopsy. Ulcerations and erosions are easily visualized. Some of the few disadvantages of endoscopy are the inability to detect functional diseases of the GI tract, real estimation of the luminal diameter as well as irritable bowel syndrome. Furthermore, the endoscope can only be inserted as far as the descending duodenum in large dogs, and the very proximal jejunum in small dogs and cats and only mucosa! and intraluminal disease can be detected. The main object of the workshop is to introduce this diagnostic procedure to the practitioners, to explain the technique, its' benefits and limitations and to enable a workout for the practitioners on animal model as well as on a live animal.
Workshop - oral presentation